Social and Economic Rights in the German Basic Law? An Analysis with Respect to Jurisprudence of the Federal Constitutional Court - Christoph Enders (Constitutional Review, 2020)
The Basic Law for the Federal Republic of Germany did originally not provide for social or economic rights understood as claims to benefits. The Federal Constitutional Court (FCC) did, indeed, recognise the states obligation to protect individuals against assault by others (right to security) and further ruled that everyone has the right to use facilities provided by the state under equal conditions (right to participation). These rights, however, aim to ensure that the state uses existing means as intended. In addition, the FCC by now has recognised a “right to the guarantee of a dignified minimum subsistence”. It is an original entitlement as the state is obliged to create and provide benefits for individuals in need. This new legal construction, however, misconceives the division of responsibilities between the FCC and the legislator and collides with the principle of the separation of powers